Business Feasibility Analysis of RBT Wedding Decoration Using the Payback Period (PP) and Profitability Index (PI) Methods - Shaila, Syarifah; Dyah Setyaningsih, Eka; Islami, Vina (Sean Institute, 2025)
The purpose of this study is to determine how long it takes for RBT Wedding Decoration to reach the payback period (PP) and the ratio of the Profitability Index (PI) it has, so that the business can be categorized as feasible to run. The method used in this study is a non-statistical quantitative method. The population and sample in this study are all financial report data from RBT Wedding Decoration from September 2015 to December 2019. The sampling technique used is a non-probability sampling technique. Data collection techniques used in this study are interviews and documentation techniques. This study's data analysis technique uses a non-statistical or descriptive quantitative method. The results of this study indicate that the time needed by RBT Wedding Decoration to return investment funds or capital is 36.24 months or 3 years and 8 days, with a Profitability Index ratio of 1.61, where this ratio indicates that RBT Wedding Decoration is feasible to run.